The Effect of Oregano (Origanum vulgare) Leaf Extract on Selected Clot-Based Assays - Salvatierra, Kyian Crista Leonardo; Peñaranda, Krishna Racel Lumabas; Pontanares, Jessica Ibañez; Salazar, Edchelle Mendoza; Tiagan, Nicolette Dumalaog; Villanueva, Andrew Josef Eleosida; Vinluan, Von Johnson Meer; Wong, Jazmine Faith Santiago; Laranang, Ariane Tesorero; R, RMT; M, MSMT (Asian Journal of Biological and Life Sciences)
Aim: This study investigates the anticoagulant capabilities of Oregano (Origanum vulgare) leaf extract using clot-based tests. Materials and Methods: Fifteen (15) healthy male volunteers completed medical assessments and had blood samples collected through venipuncture. The components of oregano leaves were identified by subjecting them to methanol extraction. Prothrombin Time (PT) and activated Partial Thromboplastin Time (aPTT) assays were performed on the human plasma samples, each repeated three times. Results: The results demonstrated a substantial increase in the PT and aPTT at extract doses of 25 mg/mL, 50 mg/mL, and 100 mg/mL. There were notable differences in the results between the ideal concentration (50 mg/mL) and the baseline control (0 mg/mL) for PT, as well as between the ideal concentration (25 mg/mL) and the baseline control for aPTT. There also were significant differences between the concentrations of the extract and the baseline control for both PT and aPTT. Conclusion: The results indicate that the leaf extract of O. vulgare has an anticoagulant effect and can potentially prevent blood clotting. Future research should focus on analyzing outcomes in distinct demographic groups, investigating alternate clot-based examinations, and exploring the chemical makeup of O. vulgare for pharmaceutical and medical laboratory applications.
Keywords: Anticoagulation; Clot-based assays; Flavonoids; Origanum vulgare.